CUSTOMER LOYALTY FROM PERSPECTIVE OF MARKETING MIX STRATEGY AND CUSTOMER SATISFACTION A study from Grab - Online Transportation in Era of Industrial Revolution 4.0 - Ade Permata Surya (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
ABSTRACT. This study aims to examine and analyze the influence of marketing mix 7P (product, price, promotion, place, people, physical evidence, and process) on costumer loyalty with the mediating role of customer satisfaction. A lesson from case of overlapping online transportation user base in Indonesia, specificly from Grab’s Consumer perspective. The research was design by using conclusive experiment, in casual type, with quantitative and survey methods. The sampling method used is sampling judgmental and the data was analized by SEM-PLS with WarpPLS 6.0. Data was taken by giving questionaire to 406 respondents. Respondents are Grab’s consumer. The result shows that the variable such as price, promotion, place, people, and process were significantly positif give effect to customer satisfaction, and customer satisfaction affected customer loyalty positifly and significantly.  In other hand, product and physical evidence were not significantly give effect. Adjusted R-squared coefficients of customer satisfaction and customer loyalty were 0,540 and 0,512 which means 54% of customer satisafction can be made by marketing mix variables and 51,2% of customer loyalty can be made by customer satisfaction. The future research in the same topic can use probability sampling method, especially stratified random sampling, and researcher can compare to another ASEAN countries’ data to enhance the more meaningful insight.Key words: marketing mix, customer satisfaction, customer loyalty, online transportation. ABSTRAK. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh bauran pemasaran 7P (product, price, promotion, place, people, physical evidence, and process) terhadap loyalitas pelanggan dengan peran mediasi kepuasan pelanggan. Pelajaran dari kasus tumpang tindih basis pengguna transportasi online di Indonesia, khususnya dari perspektif konsumen Grab. Penelitian ini dirancang dengan menggunakan eksperimen konklusif, dalam tipe kasual, dengan metode kuantitatif dan survei. Metode pengambilan sampel yang digunakan adalah sampling judgmental dan data dianalisis dengan SEM-PLS menggunakan bantuan WarpPLS 6.0. Data diambil dengan memberikan kuesioner kepada 406 responden. Responden adalah konsumen Grab. Hasil penelitian menunjukkan bahwa variabel seperti price, promotion, place, people, dan process berpengaruh positif signifikan terhadap kepuasan pelanggan, dan kepuasan pelanggan mempengaruhi loyalitas pelanggan secara positif dan signifikan. Di sisi lain, product dan physical evidence tidak berpengaruh signifikan. Koefisien Adjusted R-squared pada kepuasan pelanggan dan loyalitas pelanggan adalah 0,540 dan 0,512 yang berarti 54% dari kepuasan pelanggan dapat dibuat oleh variabel bauran pemasaran dan 51,2% dari loyalitas pelanggan dapat dibentuk oleh kepuasan pelanggan. Penelitian di masa depan dalam topik yang sama dapat menggunakan metode sampling probabilitas, khususnya pengambilan sampel bertingkat, dan peneliti dapat membandingkan dengan data negara-negara ASEAN lainnya untuk meningkatkan masukan yang lebih bermakna.Kata kunci: Kepuasan pelanggan, Kualitas layanan, loyalitas pelanggan, transportasi online.